State Defense in Nationalism and National Integration Perspective - Ariesani Hermawanto; Sri Muryantini; Agussalim Agussalim (Syntax Corporation Indonesia, 2023)
Nationalism and defending of state are closely related. Nationalism is pride in one's own nation that offers insight into nationalism, which is described as a form of 'patriotism'; a pride when individuals identify themselves as a collectivity in a nation. The defending of state is a form of a sense of belonging to citizens which is an important aspect to maintain the existence of a nation-state. Defending of state has a very broad dimension, and not limited to physical elements, but essentially is the inculcation of nationalist values. The issues raised are related to defending of state through the cultivation of a spirit of nationalism and its implications for the process of national integration. The method used here is to observe various literature related to the subject matter raised, either in the form of books, papers or useful writings so that they can be used as guidelines in the research process. This research focuses on the study and analysis of defending the country through strengthening the values of nationalism based on a sense of belonging, and its relation to the process of national integration. The results of this study indicate that defending the country is based on a strong awareness of being a state, so that people in a country can uphold their country and are willing to defend it from various threats. Defending of state is an important tool for the success of the national integration process which is a form of state existence that can be maintained.